Bentuk Evaluasi Belajar SDIT Global Cendikia - Miftahul Jannah Alfarizi; Shabrina Shabrina (AS-SABIQUN, 2020)
This research is motivated by the problem that there is no defivinitive learning evaluation standard for children who have advantages and disadvantages even though they get aducational services in incluve classes. Therefor,this study aims to find solutions to solving problems of learning evaluation planning systems, forms of evaluation forms of reporting of evaluation results. Which is included in the inclusive class of this study is focused on planning the evaluation of learning, the form of evaluation carried out, and the form of evaluation reports that have been carried out in inclusive classes contained in the GLOBAL CENDEKIA SCHOOLAR this research was conducted by interview, observation, documentation methods.